The Integration of Aqidah, Morals, and Sufism in Islamic Education - Nafsiyah, Faizatun; Paramita, Laura; Sutanti, Dini; Nursalim, Eko; Khojir, Khojir (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study explores the integration of faith (‘aqidah), ethics (akhlaq), and Sufism (tasawwuf) as the foundational elements in cultivating comprehensive religious awareness among Muslims. Employing a qualitative methodology through a literature review, the research delves into the historical, philosophical, and conceptual interplay of these three dimensions and underscores their collective significance in addressing the challenges posed by modernity, secularism, and moral relativism. While ‘aqidah establishes the core beliefs of a Muslim, akhlaq guides social and interpersonal conduct, and tasawwuf nurtures the spiritual depth and inner purification. Historically, the compartmentalization or neglect of one or more of these aspects has resulted in an imbalanced understanding and practice of Islam, often diminishing its transformative potential. This paper argues that a holistic integration of these three pillars is essential for developing a well-rounded Muslim identity—one that is intellectually grounded, ethically responsible, and spiritually conscious. Furthermore, integrative character education rooted in Islamic teachings is presented as a strategic and sustainable model for nurturing rational, moral, and spiritually aware individuals in contemporary contexts. The findings highlight the need to revisit classical Islamic educational frameworks and adapt them to current realities to ensure a meaningful and resilient religious life.